MANDIBULAR REPOSITIONING SPLINT: A FUNCTIONAL AND ESTHETIC CONSIDERATION FOR DISC DISPLACEMENT WITH REDUCTION AND MYOFASCIAL PAIN MANAGEMENT - Theresia Nuturisa Tarigan; Ricca Chairunnisa (Journal of Syiah Kuala Dentistry Society, 2019)
Disc displacement with reduction represent the early stage of disc derangement disorders. Disc derangementdisorders result from elongation of capsular and discal ligaments coupled with thinning of the articular disc.These changes commonly result from either macro or micro trauma. Mandibular repositioning splint can be usedto treat disc displacement with reduction. This clinical report aims to explain management of disc displacementwith reduction and myofacial pain with mandibular repositioning splint. 23-years-old female patient wascomplaining in mouth limited opening and pain around cheeks, ears, neck and shoulders since six months ago,especially after wake up in the morning but returned to normal a few hours later. On clinical examinations therewas a clicking sound while mouth opening and closing, also pain during palpation on facial muscles, neck andshoulders. Patient was suggested to use mandibular repositioning splint 24 hours a day for three to six months.Mandibular repositioning splint is effective if the patient uses it continuously. Functional and esthetic concernsare important if the mandibular repositioning splint is to be used during the day. The advantages of themandibular repositioning splint are least affected of speech function, more esthetic and the patient easier to movethe mandible to posterior. Mandibular repositioning splint is the best choice for disc displacement and myofascialpain treatment because it may be more acceptable from a functional and esthetic standpoint. Keywords : Disc displacement with reduction, Myofascial pain, Mandibular repositioning splin